Effectiveness of Physiotherapy Interventions on Achilles Tendinopathy - Paramita, Dewa Ayu Made Dhyana Pradnyan; M. Widnyana (Kinetic and Physiotherapy Comprehensive, 2022)
Background: Achilles tendinopathy is a clinical condition characterized by local pain, swelling in and around the Achilles tendon, and impaired function due to overuse or intrinsic factors such as being overweight. This disorder is often found in individuals who participate in physical activities such as running and jumping. Pain is felt during activity and subsides after rest, but if this continues, the pain may persist even at rest resulting in further decreased performance. Physiotherapy interventions for managing Achilles tendinopathy are quite varied, starting from the application of modalities and exercise and manual therapy.   Objective: To determine the effectiveness of physiotherapy intervention in Achilles tendinopathy.   Methods: The method in this study is a literature review or literature review using secondary data in the form of a review of research articles related to the effectiveness of physiotherapy interventions in Achilles tendinopathy through the search engines google scholar, PubMed, and Science Direct.   Results: Several studies have shown that physiotherapy interventions, except for low-level laser therapy (LLLT), effectively reduce symptoms of Achilles tendinopathy.   Conclusion: Physiotherapy interventions such as eccentric exercise and a combination of eccentric exercise with soft tissue treatment, pressure massage, and ESWT are effective in reducing symptoms in patients with Achilles tendinopathy.